Categories of Threats and Attacks to Various Information Services (Trinity Journal of Management, IT & Media (TJMITM), 2020)
The growth of information technology has revolutionized the whole world. It has actually changed the way of communication, of doing business, of transacting and even of thinking. The impact of information technology especially internet is visible everywhere in almost all domains like hospitality, education, banking, etc. TheSecurity of Information systems is being highly challenged by the propagation of web -based applications including e-commerce and a variety of information services. Information systems are oftenunprotected to variety of threats which leads to harms that might resultinto significant financial losses. It ranges from small fatalities to entire information system demolition. It is essential that security of an information system should protect the confidentiality, integrity, and availability of the system. Now a day, organizations are struggling to understand what the threats to their information assets are and how to obtain the necessary means to counter them which continues to pose a challenge. Further improve our understanding of security threats;this paper addresses   a security threat classification model which allows us to study the threats class impact over time. This paper also proposes different criteria of information system security risks classification and gives a review of most of the threat classification models. It defines a model for information system security threat classification in order to propose a classification architecture that supports all threat classification principles and helps organizations implement their information security system.
Keywords: Information system security; Threat classification; Threat; criteria; security risk; Threat Impact